SOME ASPECTS FOR MODERN SOLUTIONS FOR STRENGTHENING SOCIAL RESILIENCE AS GUARANTEE FOR THE FUTURE WELL-BEING OF AN OPEN AND INCLUSIVE SOCIETY - Sloka, Biruta; Tora, Ginta; Dzelme, Juris; Buligina, Ilze (University of Latvia, 2021)
Social inclusion and reduction of inequalities is becoming an increasingly topical problem in a range of OECD countries, due to the demographic structure of inhabitants and inequality of income, in many cases depending on labour contribution taking into account skills and competence often lacking for part of population gaining education many years ago. Big share of this part of the population currently is not able to keep the speed of technology development and increase of requirements for digital skills and internet use. The aim of the current research is to investigate possible solutions to address social inclusion by possible involvement in the labour market of different groups at risk – based on provision of digital skills, computer availability, as well as health conditions by regions in Latvia, by age groups, by gender, by employability status. The tasks of the research: analyse recent scientific findings on innovative approaches on involvement of different groups of inhabitants being at poverty risk into labour market and social inclusion, making them feel as valuable and esteemed members of the society; analyse data of several survey results: EU-SILC; Labour Force Survey and Survey on ICT skills for different groups of society in Latvia; analyse tendencies on Internet use in Latvia by gender. Main research methods – analysis of previous conducted research results reflected in scientific publications and policy analysis documents; analysis of data of EU-SILC and Labour Force Surveys as well as survey results on ICT skills on aspects of digitalisation and willingness to be involved in training and improvement of skills to avoid social exclusion and poverty. Findings – different regions have different results in digital literacy, however, implementation of innovative approaches in inhabitants’ involvement in labour market help to avoid or diminish social exclusion.
Keywords: Income Distribution; Government Policy and Regulation; Innovations; Technological Change; Human Resources; Research Subject Categories::SOCIAL SCIENCES::Business and economics